The Contributions of Vestibular Evoked Myogenic Potentials and Acoustic Vestibular Stimulation to Our Understanding of the Vestibular System - Rosengren, Sally M.; Colebatch, James G. (Frontiers in Neurology, 2018)
Vestibular-evoked myogenic potentials (VEMPs) are short-latency muscle reflexes typically recorded from the neck or eye muscles with surface electrodes. They are used clinically to assess otolith function, but are also interesting as they can provide information about the vestibular system and its activation by sound and vibration. Since the introduction of VEMPs more than 25 years ago, VEMPs have inspired animal and human research on the effects of acoustic vestibular stimulation on the vestibular organs, their projections and the postural muscles involved in vestibular reflexes. Using a combination of recording techniques, including single motor unit recordings, VEMP studies have enhanced our understanding of the excitability changes underlying the sound-evoked vestibulo-collic and vestibulo-ocular reflexes. Studies in patients with diseases of the vestibular system, such as superior canal dehiscence and Meniere’s disease, have shown how acoustic vestibular stimulation is affected by physical changes in the vestibule, and how sound-evoked reflexes can detect these changes and their resolution in clinical contexts. This review outlines the advances in our understanding of the vestibular system that have occurred following the renewed interest in sound and vibration as a result of the VEMP.